Costo de implantación de alfalfa pura en el Valle Inferior del Río Negro - Garcilazo, Maria Gabriela; Gallego, Juan Jose; Parra, Gustavo Aldolfo; Guerrero, Silvana Alejandra (EEA Valle Inferior, INTA, 2025)
EEA Valle Inferior